2021
DOI: 10.1177/02692163211024451
|View full text |Cite
|
Sign up to set email alerts
|

Virtual models of care for people with palliative care needs living in their own home: A systematic meta-review and narrative synthesis

Abstract: Background: Access to palliative care in the community enables people to live in their preferred place of care, which is often home. Community palliative care services struggle to provide timely 24-h services to patients and family. This has resulted in calls for ‘accessible and flexible’ models of care that are ‘responsive’ to peoples’ changing palliative care needs. Digital health technologies provide opportunities to meet these requirements 24-h a day. Aim: To identify digital health technologies that have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 71 publications
1
18
0
Order By: Relevance
“…Decision makers should ensure that technology is relevant to the needs of palliative care users, as these requirements will influence the design, use, and function of systems [ 119 , 120 ]. For example, health care professionals may generally use technology to access patient data and communicate with other professionals, whereas patients may wish to access their own health data and contact health care services.…”
Section: Discussionmentioning
confidence: 99%
“…Decision makers should ensure that technology is relevant to the needs of palliative care users, as these requirements will influence the design, use, and function of systems [ 119 , 120 ]. For example, health care professionals may generally use technology to access patient data and communicate with other professionals, whereas patients may wish to access their own health data and contact health care services.…”
Section: Discussionmentioning
confidence: 99%
“…It reportedly reduced visits by clinicians [ 12 ]. In addition, the software used in telehealth needs to be simple, effective, reliable, and safe with the highest level of security for confidentiality [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the current scoping review reported that in remote areas mobile phone coverage, reception and connectivity can be an issue. In addition, older people and digitally inexperienced patients needed to be supported to build their level of confidence and preparedness to engage with virtual care [ 39 ]. Nevertheless, the success and sustainability of telehealth are dependent on factors such as reliable and secure equipment, connectivity and clinician support, and flexibility [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent systematic reviews revealed that telehealth has been used to connect patients and their caregivers to medical professionals remotely. Examples of telehealth services are telephone consultation, telephone advice and support lines, video consultation, remote patient monitoring [19][20][21][22]. Telehealth has shown to be extremely useful resource for palliative care providers working in rural communities.…”
Section: Plos Onementioning
confidence: 99%